The treatment of allergic rhinitis improves the recovery from asthma and upper respiratory infections - Sarti, Willy; Gomes-Monteiro , Lídia Alice; Machado, Claudia Saad Magalhães (São Paulo Medical Journal, 1995)
Forty-six asthmatic children with repeated respiratory infections presented symptoms of allergic rhinitis. All patients were treated locally for allergic rhinitis either with disodium cromoglycate or beclomethasone dipropionate. After six months of treatment, 95% of the children showed improvement of allergic rhinitis and 84% improvement of bronchial asthma, as well as fewer infections. We concluded that allergic rhinitis plays an important role in facilitating infections of the upper respiratory tract, and a possible association of rhinitis, viral infections and bronchial asthma is discussed.